Performance of Canna indica and Typha latifolia in mono and mixed culture for secondary wastewater treatment in constructed wetlands with vertical flows under arid conditions (Touggourt, Algeria). Issue 1 (20th December 2022) - Zorai, Ameur; Benzahi, Khedidja; Labed, Brahim; Ouakouak, Abdelkader; Serraoui, Mabrouk; Bouhoreira, Abdelaziz
Abstract: This work investigates three laboratory-scale vertical flow-constructed wetlands (VFCWs) for treating a secondary effluent of wastewater under arid conditions to investigate the efficiency of two plants Canna indica and Typha latifolia in mono and mixed culture. The VFCWs were operated under hydraulic load (0.057 m 3 /m 2 d) and 5 days retention time. The results indicated no significant differences ( P > 0.05) between the mono and mixed cultures. The C. indica gives the best efficiency of pollutant removal as COD (71.34%), NO2 − (69.34%), and PO4 3− (69.67%). The uptake of TSS (83.98%) was best in the case of mixed culture. The mean percentages of BOD5 were convergent for mono and mixed culture, and it exceeds 89.80% in mixed culture. The mean percentages in NH4 + (98.69%) in mixed culture, elimination of NO2 −, and the increase in the concentration of NO3 − in the treated effluent showed the presence of nitrification in the VFCWs units. The two plant species exhibit high efficiency in the elimination of pollution compared to the unplanted control, with a slight superiority in the mixed culture. Therefore, it can be concluded that the application of these plants can be effective in arid conditions. HIGHLIGHTS: Study of some plant species (comparison) in the field of water treatment in arid regions. Comparison of monoculture and mixed. Helps in the prevention of pollution. Low-cost treatment solution for the rural areas. Helps to optimize the design of the treatment units in arid regions. Graphical Abstract